Book Review: The Quiet Power of Indicators - Measuring Governance, Corruption and the Rule of Law - John Cipperly (Oñati Socio-Legal Series)
Book review of Sally Engle Merry, Kevin E. Davis and Benedict Kingsbury, eds. The Quiet Power of Indicators, Measuring Governance, Corruption and Rule of Law. New York, NY. Cambridge University Press, 2015, pp. 369, ISBN 978-1-107-07520-7 $34.99.